2012
DOI: 10.5194/aab-55-36-2012
|View full text |Cite
|
Sign up to set email alerts
|

Meat quality traits and muscle composition of cows differing in lactation performance

Abstract: Beef and dairy cows differ in the way in which they utilise nutrients and in accretion or mobilisation of body reserves during lactation. Thus far, little is known about the impact of lactation performance on body composition, meat quality, and the related muscle structure of cows with a defined, combined beef and dairy genetic background. In the described experiment, 50 F 2 cows, originating from mating Charolais bulls to German Holstein cows and a following intercross of F 1 individuals, were slaughtered dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…To address this issue, we took advantage of a crossbreed cow population of a dairy (German Holstein) and a beef breed (Charolais), which was raised and kept under dairy production conditions (Kühn et al 2002), but predominantly showed a beef phenotype (Hammon et al 2010). In this population, Hammon et al (2010) and Hamada et al (2012) had observed a negative correlation between milk yield (MY) on one hand and body fat deposition and carcass weight on the other hand.…”
Section: Introductionmentioning
confidence: 89%
“…To address this issue, we took advantage of a crossbreed cow population of a dairy (German Holstein) and a beef breed (Charolais), which was raised and kept under dairy production conditions (Kühn et al 2002), but predominantly showed a beef phenotype (Hammon et al 2010). In this population, Hammon et al (2010) and Hamada et al (2012) had observed a negative correlation between milk yield (MY) on one hand and body fat deposition and carcass weight on the other hand.…”
Section: Introductionmentioning
confidence: 89%
“…Details were described elsewhere (Hamada et al, 2012). Briefly, heifers were reared in a free-stall barn and were inseminated at 18 months of age with semen from German Holstein sires.…”
Section: Animals and Samplesmentioning
confidence: 99%
“…Muscle fibre traits were measured and muscle fibre types were determined with an image analysis system equipped with a Jenaval microscope (Carl Zeiss, Jena, Germany), an Altra20 CCD camera (OSIS), and a special muscle fibre measurement module (MAS, Freiburg, Germany) of the Cell\^D software (OSIS). Measurement of muscle fibre traits were performed as described earlier (Albrecht et al, 2011;Hamada et al, 2012).…”
Section: Histology and Image Analysismentioning
confidence: 99%
See 2 more Smart Citations